THE ROLE OF THE MINISTRY OF FINANCE OF UKRAINE IN SHAPING STATE CUSTOMS POLICY: ECONOMIC AND LEGAL ASPECT - Ivan Yaromii (Baltic Journal of Economic Studies, 2025)
The subject of the study is to clarify the role of the Ministry of Finance of Ukraine in shaping state customs policy from both economic and legal perspectives. Research purpose: to analyze the framework of concepts and categories, examine the current state of statutory regulation, including economic component, and determine the role of the Ministry of Finance of Ukraine in shaping state customs policy. Methodology: the study employs both general and specific methods of scientific knowledge, namely, systems analysis, the dialectical method, formal logic, as well as structural and functional approaches. Results: the role of the Ministry of Finance of Ukraine in shaping state customs policy is examined from both economic and legal perspectives. The article analyzes the key functions and powers of the Ministry of Finance of Ukraine in the customs sphere, as well as its influence on the development of customs legislation and its practical implementation. Particular attention is given to the fiscal function of state customs policy and its impact on the formation of the State Budget of Ukraine. The regulatory legal acts governing the activities of the Ministry of Finance of Ukraine in the field of state customs policy are analyzed. It is noted that there are inconsistencies between the customs legislation and the normative legal acts defining the competence of the Ministry of Finance of Ukraine in shaping state customs policy that results in legal uncertainty in practice. The author emphasizes the need to strengthen the institutional capacity of the Ministry of Finance of Ukraine in shaping state customs policy. It is proposed that the term “institutional capacity of the Ministry of Finance of Ukraine” be understood as the Ministry’s ability to effectively exercise its legally defined functions and powers in order to ensure the sustainable development of the national economy, effective public finance management, and the implementation of state financial policy. It is substantiated that the institutional capacity of the Ministry of Finance of Ukraine may comprise the following components: 1) an efficient and transparent corporate structure ensuring a clear division of functions and powers; 2) talent capacity (in particular, the presence of highly qualified and motivated personnel with the relevant knowledge and skills to perform their duties); 3) information technologies for collecting, processing, and analyzing data essential for informed decision- making; 4) a well-defined and effective legal framework regulating the activities of the Ministry of Finance of Ukraine and its interaction and coordination with customs authorities; 5) international cooperation, involving active engagement in order to exchange experience and attract best practices in customs coordination and public finance management. It is concluded that strengthening the institutional capacity of the Ministry of Finance of Ukraine is essential for ensuring the sustainable development of the national economy and the effective management of public finances. The Ministry of Finance of Ukraine plays a pivotal role in shaping state customs policy, and its activities exert a significant influence on the country’s economic development.